Household hunger, poverty, and childcare in 5 states of Nigeria and their impacts on nutritional outcomes in preschool children - Manyong, Victor; Abdoulaye, Tahirou; Ojide, M.; Ogundapo, A.T.; Ayoola, G.B.; Dashiell, Kenton E.; Okike, Iheanacho (SAGE Publications, 2021)
This article presents findings from baseline surveys in 5 states of Nigeria to assess the nutritional outcomes on target groups on attaining the UN Sustainable Development Goal 2. The augmented regression technique was applied to analyze data from a sample of 1642 households with at least 1 child under the age of 5 years (U5) and their mothers or caregivers out of a total of 2500 households that were drawn from the 250 enumeration areas of the Nigeria Bureau of Statistics in the 5 states. The results support the growing evidence base that poverty and household hunger are pervasive. The incidence of poverty highlights inequalities among states. The combination of poverty and hunger was mirrored in the damning extent to which all forms of malnutrition coexisted in children U5, particularly during the second year of infancy and among poor households. Evidence from this study points to poor dietary quality of complementary food rather than other childcare practices as majorly responsible for child malnutrition. Child wellness was positively affected by maternal health-seeking behavior but negatively by the poverty probability index of the household. Notably, maternal health-seeking behavior played a more relevant role in child wellness than mothers’ educational attainment.